Floral Structure and Breeding Systems of Manglietia conifera Dandy (Magnoliaceae) - Hao, J.; Pan, L.; Jia, H.; Jiang, Q.; Pan, Q.; Pinyopusarerk, K.; Kalinganire, A. (MDPI, 2019)
Manglietia conifera Dandy is a fast-growing tree species that has been introduced to China from Vietnam, which has great potential for commercial planting. However, plantation development is hindered by a lack of seed material, due to low natural seed-set in locally grown trees. Thus, we investigated the morphological characteristics of male and female flower organs, and conducted controlled pollination to understand the breeding systems of the species. The individual flower of M. conifera is bisexual, and the stamen group is polymerized at the base of the receptacle. Pollen is symmetrically distributed on both sides. Controlled pollination suggests that apomixis does not occur in M. conifera. Results from the flower structure, pollen–ovule ratio, outcrossing index, and controlled pollination indicated that the breeding system in M. conifera was outcrossing (partially self-compatible, pollinators required), and self-incompatibility occurred in a later stage of embryonic development. Moreover, the self-incompatibility phenomenon was revealed by the abnormal germination of pollen on the stigma. This paper provides a basis for controlled pollination programs of M. conifera.